Design and Optimization of Metamaterial Antenna for Enhancing Satellite Communication - P., Arsavarthini; M.B., Faheema; S., Iniya; R., Karthika (IRO Journal on Sustainable Wireless Systems, 2026)
This paper presents the design and optimization of a multi-band antenna intended for use in satellite communications. The antenna consists of a pentagonal patch multi-band antenna that uses a metamaterial of split ring resonators to enhance its electromagnetic performance. Some disadvantages associated with conventional antennas include being large, having a limited bandwidth and producing high levels of signal reflection. The performance of the antenna is effective in the C, X, and Ku satellite communication bands. The proposed SRR-based pentagonal patch antenna has a low level of reflection with S11<-10dB; a gain of 4.96dB; and a VSWR<2 indicating that very little of the transmitted signal will be reflected back from the antenna. The radiation pattern of the proposed antenna is also very concentrated in 2D space, resulting in higher signal strength and lower interference. Ansys HFSS simulation of the proposed antenna design indicated potential applications for satellite internet, global positioning, remote sensing, and Internet of Things (IoT) systems. Because of its low weight, low cost, and scalable design characteristics, the proposed antenna is expected to be fully compatible with next generation satellite systems. Future improvements to the proposed antenna may include adaptive beamforming and tunable metamaterials to further enhance its satellite communication capabilities.